Breaking through the Cracks: On the Mechanism of Phosphoric Acid Migration in High Temperature Polymer Electrolyte Fuel Cells. Issue 14 (25th October 2018) - Halter, J.; Marone, F.; Schmidt, T. J.; Büchi, F. N.
Abstract : In high temperature polymer electrolyte fuel cells, at high current densities, phosphoric acid (PA) migrates toward the anode and invades catalyst, microporous and gas diffusion layers (GDL). This work studies this PA redistribution using synchrotron based operando X-Ray tomographic microscopy (XTM) and electrochemical impedance spectroscopy (EIS) during a current cycling protocol. It is shown that under reformate conditions, during the first 2 minutes after a positive current step, the cell voltage increases due to better wetting of the anode catalyst layer (CL). From 2 to 20 minutes, the cell voltage drops due to increasing mass transport losses in the microporous layer (MPL) and the GDL. At the anode, cracks in MPL and CL, both with widths up to 150 μm, are flooded within 2 minutes after a current density increase. Acid flooding is only observed for MPL cracks that overlap with CL cracks. The CL cracks therefore act as injection points for the flooding of the MPL cracks and the gas diffusion layer. No change in the PA content of any of the cathodic porous components was observed.